2017
DOI: 10.1371/journal.pone.0186835
|View full text |Cite
|
Sign up to set email alerts
|

Late presentation of HIV infection in the country of Georgia: 2012-2015

Abstract: Late presentation for HIV care has important individual and population implications. The objective of this study was to explore the problem of late presentation in the country of Georgia. Data on adult persons newly diagnosed with HIV in Georgia between 2012 and 2015 were extracted from the national AIDS Health Information System. Late presenter was defined as a person diagnosed with HIV with a CD4 cell count <350 cells/mm3 or an AIDS defining illness regardless of the CD4 cell count in the six months after HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
6
16
0
Order By: Relevance
“…Also, in the latest ECDC study from 2017 across the WHO EU Region, the proportion of individuals diagnosed late increased with age . In our study, increased risks of late entry and advanced disease were observed for PWID, in line with data reported for other European cohorts .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, in the latest ECDC study from 2017 across the WHO EU Region, the proportion of individuals diagnosed late increased with age . In our study, increased risks of late entry and advanced disease were observed for PWID, in line with data reported for other European cohorts .…”
Section: Discussionsupporting
confidence: 93%
“…Other European studies also noted high proportions of subjects presenting late . Similar trends of late entry to care were reported in the large Collaboration of Observational HIV Epidemiological Research Europe (COHERE) study for the period of 2001–2010, which does not include Polish data.…”
Section: Discussionsupporting
confidence: 69%
“…Specifically, in the country of Georgia, TB remains the leading cause of death in PLWH [8]. A combination of factors, including increasing HIV prevalence and drug-resistant TB, high rates of late HIV diagnosis, and overlapping risk factors for TB and HIV, makes Georgia particularly vulnerable to a TB/HIV epidemic [6, 9, 10]. In order to alleviate both morbidity and mortality associated with TB in PLWH, active case finding (ACF) for TB has been recommended as a strategy for regions with high TB and HIV incidence [7, 11–13].…”
mentioning
confidence: 99%
“…AHI is associated with transient levels of high-titer viremia [1,3], which is a driver of HIV transmission among men who have sex with men (MSM) in the United States. Diagnosis of AHI has been associated with a reduction in risk behavior [4] and could prevent later presentation and treatment initiation, which is associated with worse outcomes [5][6][7]. Additionally, treatment initiation during AHI preserves immune function [8] and limits HIV reservoirs compared to later treatment [9].…”
mentioning
confidence: 99%